Rancang Bangun Inverter Mengubah Arus Listrik DC ke AC Berbasis Arduino Uno - Risky Binsar Pandapotan Simanjuntak; M Safii; Fitri Anggraini; Sumarno Sumarno; Indra Gunawan (Journal of Computer System and Informatics (JoSYC), 2021)
At this time electrical energy is needed in terms of helping humans in carrying out their activities both in doing their daily work. In this case, it is impossible for there to be problems in periodic blackouts to save electricity resources carried out by PLN and to disrupt all human activities starting from the tools that require electrical energy. For this reason, it is necessary to anticipate by making an inverter which aims to make all the activities they do using electrical energy are not disturbed. This tool is assisted by using Arduino Uno as the main ingredient which later DC electrical energy, namely the battery, will convert electrical energy that we usually use AC electrical energy